(untitled) (Educational Perspectives Magazine (REPED), 2022)
In this research a proposal for the teaching and leaming of Thales’ theorem through problem-solving is presented. It arises from the analysis of the approaches, in both, the Chilean and French secondary education systems towards this matter, within the framework of the Study Abroad Program for people studying to become Mathematics teachers, developed by the Teacher Training Institute from the University of Toulouse, in France. The main pillars considered in this study are, the low levels of achievement accomplished by geometry students (Corberan, et al, 1994) and the importance attributed to problem-solving (Gaulín, 2001; Aravena, 2009; Pólva, 1990). The objective of this proposal is to get the students to leam to deal with mathematical contents by using problem-solving. By doing this, it is intended to train students, who are more active participants in their own teachingleaming process. In order to attain this objective we have posed a number of problematic situations, both in the introduction to the topic, and in the class activities and evaluations. It is also done so in the demonstration of Thales’ theorem.